Cotton miR319b-Targeted TCP4-Like Enhances Plant Defense Against Verticillium dahliae by Activating GhICS1 Transcription Expression - Jia, Pei; Tang, Ye; Hu, Guang; Quan, Yonggang; Chen, Aimin; Zhong, Naiqin; Peng, Qingzhong; Wu, Jiahe (Frontiers in Plant Science, 2022)
Teosinte branched1/Cincinnata/proliferating cell factor (TCP) transcription factors play important roles in plant growth and defence. However, the molecular mechanisms of TCPs participating in plant defence remain unclear. Here, we characterised a cotton TCP4-like fine-tuned by miR319b, which could interact with NON-EXPRESSER OF PATHOGENESIS-RELATED GENES 1 (NPR1) to directly activate isochorismate synthase 1 (ICS1) expression, facilitating plant resistance against Verticillium dahliae. mRNA degradome data and GUS-fused assay showed that GhTCP4-like mRNA was directedly cleaved by ghr-miR319b. Knockdown of ghr-miR319b increased plant resistance to V. dahliae, whereas silencing GhTCP4-like increased plant susceptibility by the virus-induced gene silencing (VIGS) method, suggesting that GhTCP4-like is a positive regulator of plant defence. According to the electrophoretic mobility shift assay and GUS reporter analysis, GhTCP4-like could transcriptionally activate GhICS1 expression, resulting in increased salicylic acid (SA) accumulation. Yeast two-hybrid and luciferase complementation image analyses demonstrated that GhTCP4-like interacts with GhNPR1, which can promote GhTCP4-like transcriptional activation in GhICS1 expression according to the GUS reporter assay. Together, these results revealed that GhTCP4-like interacts with GhNPR1 to promote GhICS1 expression through fine-tuning of ghr-miR319b, leading to SA accumulation, which is precepted by NPR1 to increase plant defence against V. dahliae. Therefore, GhTCP4-like participates in a positive feedback regulation loop of SA biosynthesis via NPR1, increasing plant defences against fungal infection.